2023
DOI: 10.1200/jco.22.01365
|View full text |Cite
|
Sign up to set email alerts
|

Idecabtagene Vicleucel for Relapsed/Refractory Multiple Myeloma: Real-World Experience From the Myeloma CAR T Consortium

Abstract: PURPOSE Idecabtagene vicleucel (ide-cel) is an autologous B-cell maturation antigen–directed chimeric antigen receptor T-cell therapy approved for relapsed/refractory multiple myeloma (RRMM) on the basis of the phase II pivotal KarMMa trial, which demonstrated best overall and ≥ complete response rates of 73% and 33%, respectively. We report clinical outcomes with standard-of-care (SOC) ide-cel under the commercial Food and Drug Administration label. METHODS Data were retrospectively collected from patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
102
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(109 citation statements)
references
References 25 publications
7
102
0
Order By: Relevance
“…Patients with previous exposure to anti-BCMA therapy, high-risk cytogenetics, Eastern Cooperative Oncology Group performance status ≥ 2 at lymphodepletion and young age had inferior PFS. Authors concluded that outcomes of ide-cel in a real-world setting were comparable to those reported by KarMMa, confirming its safety and efficacy [ 142 ].…”
Section: Available Therapeutic Modalitiesmentioning
confidence: 53%
“…Patients with previous exposure to anti-BCMA therapy, high-risk cytogenetics, Eastern Cooperative Oncology Group performance status ≥ 2 at lymphodepletion and young age had inferior PFS. Authors concluded that outcomes of ide-cel in a real-world setting were comparable to those reported by KarMMa, confirming its safety and efficacy [ 142 ].…”
Section: Available Therapeutic Modalitiesmentioning
confidence: 53%
“…Second, an important point regarding baseline characteristics is that all patients in the pivotal KarMMA trial were required to be refractory to the last line of regimen before CAR T-cell therapy. 5 However, in this study by Hansen et al, 1 approximately two thirds of patients had refractory disease. Hence, further clarification on whether the remaining one third proceeded to CAR T without actively progressing myeloma is essential to contextualize the efficacy results.…”
mentioning
confidence: 55%
“…They may develop acute respiratory distress syndrome (ARDS) and thrombotic complications that can induce high in-hospital mortality [ 25 ]. This is due to MM patients’ advanced age, co-existing medical conditions, as well as to humoral and cellular immunity compromised by the disease itself and by concomitant, often prolonged-applied targeted and immunosuppressive therapies, including steroids, monoclonal antibodies [ 26 , 27 ], ASCT [ 28 ], and novel cellular therapies [ 29 , 30 ]. Furthermore, MM patients often show low/suboptimal rates (in terms of percentage of responders and magnitude of response) of both humoral and functional T-cell immune responses to anti-SARS-CoV-2 vaccines [ 31 – 34 ]; this further contributes to an increased risk of severe COVID-19, need of hospitalization and higher mortality rates [ 35 ].…”
Section: Methodsmentioning
confidence: 99%